TAX AVOIDANCE PRACTICES ON THE INDONESIAN STOCK EXCHANGE - Emma Saur Nauli Sipayung; Yoana Aulia Putri; Deliza Henny; Harti Budi Yanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This research provides an overview of tax avoidance practices in public companies on the Indonesia Stock Exchange. The factors studied included CSR disclosure quality, management compensation, capital intensity and financial distress. A total of 198 firm years from the 2018 to 2020 financial statements. The results show that CSR disclosure quality, management compensation, capital intensity, and company size (control variable) have a positive effect on tax avoidance. However, financial distress has no effect on tax avoidance